2008
DOI: 10.4103/0378-6323.42905
|View full text |Cite
|
Sign up to set email alerts
|

An open labeled, comparative clinical study on efficacy and tolerability of oral minipulse of steroid (OMP) alone, OMP with PUVA and broad / narrow band UVB phototherapy in progressive vitiligo

Abstract: Our study compared four treatment modalities in vitiligo patients, out of which oral minipulse of steroids (OMP) only had an adjunct value and was not very effective by itself. Narrow band UVB has a definite edge over broad band UVB and should be preferred when both options are available. NB-UVB and PUVA showed comparable efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Subsequently, few trials on the use of OMP therapy in vitiligo have been published by other researchers with similar results (Table 3). [13][14][15][16][17][18][19][20] The present study showed good efficacy of low-dose dexamethasone OMP in controlling disease activity, with more than 90% of patients achieving an arrest of disease activity. When the duration of therapy was increased to 9 months in patients not showing an adequate response, the success rate approached 95%.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequently, few trials on the use of OMP therapy in vitiligo have been published by other researchers with similar results (Table 3). [13][14][15][16][17][18][19][20] The present study showed good efficacy of low-dose dexamethasone OMP in controlling disease activity, with more than 90% of patients achieving an arrest of disease activity. When the duration of therapy was increased to 9 months in patients not showing an adequate response, the success rate approached 95%.…”
Section: Discussionmentioning
confidence: 94%
“…However, we combined NBUVB with oral MPD mini-pulse therapy with the aim of maximizing control and repigmentation of vitiligo. In 2008, Rath et al [22] published a study comparing the efficacy of oral mini-pulse therapy alone or combined with PUVA, broad-band UVB and NBUVB in generalized vitiligo. In their study, marked improvement was observed at 3 months in 37% of patients having received NBUVB plus oral mini-pulse therapy, 8% of patients having received broad-band UVB plus oral mini-pulse therapy, 18.4% of patients having received PUVA plus oral mini-pulse therapy and 5% of patients having received oral mini-pulse therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…In vitiligo, topical corticosteroids are the first-line treatment in the extra-facial areas (barring intertriginous and genital sites) [153]. Pulse therapy (2 consecutive days/week) with betamethasone 0.1 mg/kg for 3 months, followed by tapering of the dose by 1 mg every month over the following 3months, is a possible therapeutic option in cases of progressive generalized disease [154].…”
Section: Dermatologic Disordersmentioning
confidence: 99%